Effect of Alkaline Catalyst Concentrations and Weight Ratios of Oil to Methanol on the Biodiesel Production From Waste Cooking Oil - Anggi Dwi Chandrika; Muhammad Yerizam; Anerasari Meidinariasty (Indonesian Journal of Chemical Science, 2023)
The effect of alkaline catalyst and raw material ratio for the transesterification reaction of used cooking oil that has been previously processed has been investigated. The research was conducted by reacting the waste cooking oil with methoxy solution to obtain biodiesel. The purpose of the research was to obtain the optimum condition of the transesterification reaction, the best percent yield, and the compounds contained in the biodiesel and to compare the biodiesel obtained with SNI 7182:2015 based on the parameters of density, acid number, flash point, and cetane number. Based on the results of the study, the optimum condition obtained was at a ratio of 1:12 with a 2% KOH alkali catalyst and a yield of 92.65%. The biodiesel quality test results meet the standard requirements according to SNI 7182: 2015 with a density value of 0.86 gr/cm3, viscosity of 4.205 cSt, acid number 0.23 mgKOH/g, flash point 176.2 oC, and cetane number 68.2. The results of GCMS analysis showed 9 peaks identified with the main components of the compounds contained were hexadecanoic acid, methyl ester; 9,12-octadecadienoic acid, methyl ester; 9-octadecenoic acid, methyl ester.